Desain Lingkungan Bahasa Arab Berbasis Cooperative Learning untuk Meningkatkan Kemahiran Berbicara Arab Mahasiswa - Mahmudah, Mahmudah; Nurhadi, Nurhadi; Setiyawan, Agung; Issiyah, Iis Isti; Ramadhan, Ahmad Rizki (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to design and analyze the effectiveness of the Arabic language environment based on cooperative learning in improving students' speaking proficiency in the Arabic Language Education Study Program (PBA) UIN Sunan Kalijaga. This research uses a mixed methods approach with a sequential explanatory design, where quantitative data is collected first through pre-test and post-test to measure the improvement of students’ speaking proficiency, then continued with qualitative data collection through observation, interviews, and documentation to understand more deeply the process of implementing cooperative learning. Quantitative data analysis was conducted using a paired T-test, while qualitative data was analyzed thematically. The results showed that the cooperative learning-based Arabic environment design included learning activities such as role-play, group discussion, and jigsaw that encouraged students’ active interaction and provided more opportunities to practice speaking. Quantitatively, there was an increase in students’ speaking proficiency scores, with an average pre-test of 65 (22,97) and post-test of 80 (33,40), which showed a statistically significant difference (p-value < 0,05). Meanwhile, the qualitative results revealed that students felt more confident, motivated, and active in participating during the learning process. Supporting factors for the success of learning include cooperation between students, the role of the class, lecturers as facilitators, and a learning atmosphere that supports speaking Arabic. The obstacles faced include the students' different abilities in the group and the limited time during learning. Based on these results, it can be concluded that cooperative learning-based Arabic environment design is effective in improving students’ speaking proficiency, so it is recommended to be applied in a more structured and sustainable manner in Arabic language learning.